Mulheres camponesas e culturas do escrito: trajetórias de lideranças comunitárias construídas nas CEBS - Sonia Maria Alves de Oliveira Reis (2014)
This research aims to analyze the conditions and formative instances through which peasant women and CEBs leaders, who rarely or never attended school, built their participation in written cultures. For this reason we tried to analyze the profile of a group of six peasant women according to their social and economic family situation; education; age; religious and ethnic belonging. Then, the process of performance and formation of these women in the CEBs was reconstituted through the course of their lives, highlighting the participation modes in written cultures. The study is part of a research framework about the participation modes in cultural practices related to reading and writing through different socialization instances. It emerged from the assumption that there is no given written culture but a diversity of written cultures that vary depending on the context of use and learning that is not solely dependent on the written language based on the alphabetic system. As for the theoretical basis of this study, we highlight Galvão (2007, 2010), Barton and Hamilton (1998), Kleiman (2008), Souza (2009),and Kalman (2003, 2004a). The research methodology followed an orientation from the qualitative research assumptions. It was used oral stories; field diaries based on literacy events observed in the CEBs; and interviews, in order to identify ways to access written materials - what, why, how and when these women read and write. The documents analysis allowed us to contextualize and characterize the institutions involved in this research process, placing them in the past and present. In addition, the meanings, roles and conceptions that the leaders of the CEBs attribute to reading and writing are presented, specifically through some appropriation stories. By the data analysis procedures, it was possible to interpret that the different forms of participation in the writing cultures are guided in between oral and written, and memorized and understood aspects in a context in which orality is fundamental and reading and writing are necessary. These participation modes in written cultures, recurrent in the interviewees statements, are linked to their experiences, especially the participation in CEBs and militancy in social movements that they take part of, as evidenced by the data. Research results reaffirm the need to formulate Youth and Adult Education policies that incorporate experiences the subjects had constructed throughout their life trajectories around reading and writing in a more structural way. This requires investigating papers related to literacy outside the school setting or in specific groups, situated and located practices. Therefore, there may be better solutions to the needs and concerns of a particular social group depending on demands of everyday life, religious practices and citizen participation, considering different ways of learning. Finally, this analysis indicates the need for teacher training that addresses the various writing cultures in the community, without, however, prioritizing one practice over the others.